2021
DOI: 10.1111/ggi.14263
|View full text |Cite
|
Sign up to set email alerts
|

Association of FGF‐19 and FGF‐21 levels with primary sarcopenia

Abstract: Serum fibroblast growth factor (FGF)-19 and FGF-21 levels have been reported to be associated with muscle hemostasis. This study aims to explore the relationship between the levels of these markers and sarcopenia.Methods: In our single-center, cross-sectional study, patients over 65 years old presenting to the geriatric outpatient clinic were included. Patients with secondary sarcopenia were excluded. The Strength-Assistance with walking-Rising from a chair-Climbing stairs and Falls (SARC-F) questionnaire was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Fibroblast growth factor 19 (FGF19) has significant regenerative, metabolic, and anti-inflammatory properties associated with skeletal muscle growth and hypertrophy [ 245 , 246 , 247 ], while low levels of FGF19 are associated with sarcopenia [ 248 ]. FGF19 reverts obesity-induced muscle atrophy and restores irisin levels [ 249 ], thus playing a role in improving skeletal muscle health.…”
Section: Future Directionsmentioning
confidence: 99%
“…Fibroblast growth factor 19 (FGF19) has significant regenerative, metabolic, and anti-inflammatory properties associated with skeletal muscle growth and hypertrophy [ 245 , 246 , 247 ], while low levels of FGF19 are associated with sarcopenia [ 248 ]. FGF19 reverts obesity-induced muscle atrophy and restores irisin levels [ 249 ], thus playing a role in improving skeletal muscle health.…”
Section: Future Directionsmentioning
confidence: 99%
“… Was appropriate statistical analysis used? Lu L (2017) [ 20 ] × × Li C W 2019 [ 6 ] × / Bag S R 2021 [ 23 ] Jung H W 2021 [ 21 ] Ofazoglu U 2022 [ 24 ] × × / √= Yes; ×= No; /=Unclear; -=Not applicable …”
Section: Resultsmentioning
confidence: 99%
“…75 This growth factor is a downstream product in the unfolded protein response, leading to systemic inflammation and sarcopenia in the aging population. 76 Studies demonstrated that while aerobic exercise increases the expression of FGF-21, inactivity decreases its expression in skeletal muscle. 77 FGF-21 hinders osteogenesis through negatively influencing osteoblasts and inducing adipogenesis from bone marrow.…”
Section: Growth Factorsmentioning
confidence: 99%
“…Fibroblast growth factor‐21 (FGF‐21) is a myokine that is mainly linked with glucose and lipid metabolism through activating the peroxisome proliferator‐activated receptor (PPAR) pathway 75 . This growth factor is a downstream product in the unfolded protein response, leading to systemic inflammation and sarcopenia in the aging population 76 . Studies demonstrated that while aerobic exercise increases the expression of FGF‐21, inactivity decreases its expression in skeletal muscle 77 .…”
Section: Clinical Challengementioning
confidence: 99%